Alcan Pavilion (Benjamin New Co., Ltd.)
Alcan Pavilion the Alcan Pavilion and Alcan Dolphin Pool of the Montreal Aquarium - joint achievement of the City of Montreal and the Aluminum Company of Canada, Ltd. On the occasion of Expo 67